Knowledge Acquisition for Innovation: Networks of Top Managers in the European Fashion Industry - Alexander Fliaster; Sonja Sperber (European Management Review, 2019)
Past research revealed that social networks play a decisive role for the receipt of new knowledge by engineers and middle-level managers and, thus, essentially contribute to innovation. However, the question of by which network ties top managers – that is, the key organizational decision-makers – acquire which kind of innovation-related knowledge resources has not yet been explored systematically. Our paper addresses this research gap by empirically analyzing knowledge ties of top executives in the European fashion and accessories industry. We draw on the concept of relational embeddedness and focus on knowledge providers and knowledge ties of top managers. Based on this theoretical framework, we conducted 22 semi-structured interviews with top executives from 11 leading European companies within this industry. We present the main results of this explorative study and identify its important implications from both research and managerial perspective.
Keywords: 650; Innovation; knowledge networks; knowledge management; top management; fashion and accessories industry; upper echelons